Social Presence and Satisfaction in Online Learning between Indonesian and Malaysian Students - Putra, Eka (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2024)
Online learning has become increasingly popular in the educational environment, particularly after the COVID-19 pandemic. This research aims to describe the social presence and satisfaction of students in online learning, as well as examine the relationship between social presence and student satisfaction. A cross-sectional online study was conducted, involving 508 Indonesian and Malaysian postgraduate students from August 5 to October 2, 2023. Participants completed the social presence and student satisfaction scale developed by Gunawardena and Zittle. Data analysis techniques included descriptive statistics, the Man-Whitney test, the Kruskal-Wallis test, and Spearman's Rank-Order Correlation using SPSS 26.00. The social presence and student satisfaction were categorized as good, as there were no items with scores below average. Univariate analysis indicated that the online learning experience and the quality of the network in the place of residence were determining factors for the differences between the variables, while other characteristics, including the country (Indonesia and Malaysia), showed no significant differences. Correlation analysis indicated a positive relationship between social presence and student satisfaction. This research has important implications for improving the quality of online learning. Universities should consider revising their curriculum to be more ICT-friendly, helping students become familiar with using the platform. Educational policies should also focus on training and developing educators to effectively implement online learning. Additionally, government support is crucial in realizing high-quality online learning.